Effects of substrate annealing on wettability and intermetallic compound formation in Sn–3.0Cu/Cu systems - Mookam, Niwat; Kanlayasiri, Kannachai (My University, 2019)
This paper investigates the effects of Cu substrate annealing on the wettability of Sn–3.0Cu lead-free solder and the subsequent growth of the intermetallic compounds that are formed at the interface between the solder and the substrate. The annealing processes yielded various grain sizes, grain orientations, and residual strains within the substrates. Then, effects of the Cu substrates on the wetting and intermetallic formation were studied via reflow soldering using Sn–3.0Cu lead-free solder. The annealed substrates were compared to an unannealed Cu reference at soldering times of 20, 40, 60 and 120 s. The experimental results demonstrated that the substrate grain orientation, residual strain and grain size exert no influence on the solder wettability. After soldering, only a η-Cu6Sn5 intermetallic compound was observed in the interfacial layer for both the reference and annealed copper substrates. The thickness of the η-Cu6Sn5 layer was found to be independent of the substrate grain size but increased as the misorientation angle and the residual strain in the substrate increased.